2014
DOI: 10.1038/tp.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of manic and euthymic episodes identifies state- and trait-specific gene expression and STAB1 as a new candidate gene for bipolar disorder

Abstract: Bipolar disorder (BD) is a highly heritable psychiatric disease characterized by recurrent episodes of mania and depression. To identify new BD genes and pathways, the present study employed a three-step approach. First, gene-expression profiles of BD patients were assessed during both a manic and an euthymic phase. These profiles were compared intra-individually and with the gene-expression profiles of controls. Second, those differentially expressed genes that were considered potential trait markers of BD we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Although showing strong associations with broader psychosis spectrum, the underlying molecular mechanism of these risk associations are yet to be determined. Previous studies have shown that the risk SNPs are associated with expression of GLT8D1, ITIH4, or STAB1 in different studies [20,22], and further investigations are needed.…”
Section: Itih3/4 Rs2239547mentioning
confidence: 99%
See 1 more Smart Citation
“…Although showing strong associations with broader psychosis spectrum, the underlying molecular mechanism of these risk associations are yet to be determined. Previous studies have shown that the risk SNPs are associated with expression of GLT8D1, ITIH4, or STAB1 in different studies [20,22], and further investigations are needed.…”
Section: Itih3/4 Rs2239547mentioning
confidence: 99%
“…Notably, rs2239547 is located in an extensive linkage disequilibrium (LD) block region that contained many genes and numerous high-linked SNPs [9]. In addition to schizophrenia, these risk loci also confer risk of bipolar disorder [19][20][21]. Although showing strong associations with broader psychosis spectrum, the underlying molecular mechanism of these risk associations are yet to be determined.…”
Section: Itih3/4 Rs2239547mentioning
confidence: 99%
“…In this way, we found one gene stabilin 1 (STAB1) might contribute to schizophrenia susceptibility previously identified by pathway analysis 57 . Another study suggested that STAB1 is a new candidate gene for bipolar disorder combining of gene through expression and GWAS data 58 . Most noteworthy, we confirmed the importance of the NEK4-ITIH1-ITIH3-ITIH4 region locating in 3p21.1 (including PBRM1, STAB1) in the pathogenesis of psychiatric disease 41,42,59 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several gene‐wide association (GWA) studies have provided information on candidate genes that may predispose one to bipolar disorder and/or schizophrenia. Initial findings, that were subsequently replicated, suggested a candidate locus in chromosome 3p21, a region encompassing the genes NEK4‐ITIH1‐ITIH3‐ITIH4 . Inter‐α‐trypsin‐inhibitor (ITIH)1, ITIH3 and ITIH4 are members of the inter‐α‐inhibitor family, which has matrix stabilizing and anti‐inflammatory properties …”
Section: Introductionmentioning
confidence: 99%
“…Initial findings, that were subsequently replicated, suggested a candidate locus in chromosome 3p21, a region encompassing the genes NEK4-ITIH1-ITIH3-ITIH4. [3][4][5][6] Inter-α-trypsin-inhibitor (ITIH)1, ITIH3 and ITIH4 are members of the inter-α-inhibitor family, which has matrix stabilizing and anti-inflammatory properties. 7 Inter-α-inhibitor heavy chains ITIH1 and ITIH3 exist only in a complex with the light chain protein bikunin, which confers the trypsin-inhibitory activity that gives the protein its name.…”
Section: Introductionmentioning
confidence: 99%